Designing Project Stakeholder Management Plan at Coffee Plant Construction Project for Sucessful Initiating Phase in Ciwidey - Kusumasari, Tien Fabrianti; Pratami, Devi; Puspitasari, Nurfitri Ayu; Haryono, Imam (School of Industrial and System Engineering, Telkom University, 2017)
CV Trianom Agrotektur is a company engaged in coffee industry. Due to high demand and expanded business process the company owner is going to build a new plant in Ciwidey. The current plant cannot cover the whole business process of in processing coffee beans. The extensification towards the plant requires some guidance to lead the successful contruction project. However, building plants in rural area is not a simple thing. There should be some investigation towards stakeholders’ needs/interests or requirements. The project should also face an issue pertaining to management, i.e. how to manage stakeholders who still keep their local tradition. This study is aimed at designing project stakeholder management plan based on PMBOK 5 edition. The study shows that there are 21 stakeholders classified in 4 quadrants. Those stakeholders will be managed based on their power and interest level. Keywords— Stakeholder, Communication, Project, Coffee Plant